2019
DOI: 10.1016/j.bjpt.2018.11.007
|View full text |Cite
|
Sign up to set email alerts
|

The impact of gynaecological cancer treatment on physical activity levels: a systematic review of observational studies

Abstract: Background: The natural history of physical activity levels during and following gynaecological cancer treatment is not well understood. This is required in order to establish the time at which physical activity levels are lowest in order to target cancer rehabilitation or exercise interventions in gynaecological cancer population accordingly. Objectives: To conduct a systematic review to evaluate the impact of gynaecological cancer treatments on physical activity levels and to summarise the pattern of changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 83 publications
(121 reference statements)
0
24
0
1
Order By: Relevance
“…A recently published review, including six studies (n=1607), also supports the claim that gynecological cancer survivors report low physical activity levels compared to before treatment. Two years after treatment, 91% of the gynecological cancer survivors were not meeting physical activity guidelines, and three years after treatment 58% still reported that they were less physically active than before cancer treatment (111).…”
Section: Physical Activity For Cancer Survivorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently published review, including six studies (n=1607), also supports the claim that gynecological cancer survivors report low physical activity levels compared to before treatment. Two years after treatment, 91% of the gynecological cancer survivors were not meeting physical activity guidelines, and three years after treatment 58% still reported that they were less physically active than before cancer treatment (111).…”
Section: Physical Activity For Cancer Survivorsmentioning
confidence: 99%
“…Stevison et al report in a study from 2014 that prostate cancer survivors were those who best met the recommendations for physical activity (30%), while gynecological cancer survivors reported the lowest levels of physical activity, at only 12% of the 26 indi-viduals studied (123). Furthermore, a recent review concludes not only that gynecological cancer survivors report lower levels of physical activity than before treatment, but also that most gynecological cancer survivors did not even meet the physical activity guidelines two years after treatment (111). The finding that decreased incontinence after pelvic cancer rehabilitation did not facilitate PCS to exercise more frequently further indicates that incontinence is not the only barrier to physical activity after pelvic cancer treatment.…”
Section: Physical Activitymentioning
confidence: 99%
“…9 Women's health physical therapists and other healthcare professionals should encourage all women to practice regular physical activity. However, although the literature has consistently indicated the benefits of regular physical activity for cancer survivors, a systematic review showed that levels of physical activity remained low in gynecological cancer survivors up to three years after diagnosis 11 .…”
Section: The Brazilian Journal Of Physical Therapy (Bjpt) Special Issmentioning
confidence: 99%
“…A cancer diagnosis has been suggested to be a 'teachable-moment' which has the potential to motivate patients to make healthy lifestyle changes [8]. Even though 30-60% of cancer survivors change their lifestyle post-diagnosis, adherence to recommendations for physical activity and diet remains relatively low as compared with the cancerfree population [9,10]. Moreover, adherence to recommendations among cancer survivors has been found to decrease over time [11].…”
Section: Introductionmentioning
confidence: 99%